Sistem Informasi Pengolahan Data Perpustakaan Sekolah Smk Negeri 5 Kota Bengkulu - Amanda Olivia Firasti; Achmad Fikri Sallaby; Venny Novita Sari (Jurnal Media Computer Science, 2026)
School libraries play an important role in supporting the learning process, but library data management at SMK Negeri 5 Bengkulu City is still done manually. This situation leads to various issues, such as slow administrative processes, risks of data errors, and difficulties in tracking book inventory and loan activities. To address these issues, this study aims to develop a web-based Library Data Processing Information System using PHP programming language and MySQL database. The research method used is the Software Development Life Cycle (SDLC) with a Waterfall approach, consisting of the following stages: requirements analysis, system design, coding, testing, and implementation. The system is designed to facilitate administrators in managing book data, member information, borrowing, and returns, as well as generating reports automatically. System testing was conducted using the Black Box method, which demonstrated that all features function properly according to user needs. The result of this research is an information system that can improve the efficiency and accuracy of library management, reduce manual errors, and simplify the report generation process. Thus, this system is expected to be a solution to library management problems at SMK Negeri 5 Bengkulu City and serve as a reference for the development of similar systems in the future.